Specific interaction between mycobacterium tuberculosis lipoprotein-derived peptides and target cells inhibits Mycobacterial entry in vitro (2014)
Tuberculosis (TB) continues being one of the diseases having the greatest mortality rates around the world, 8.7 million cases having been reported in 2011. An efficient vaccine against TB having a great impact on public health is an urgent need. Usually, selecting antigens for vaccines has been based on proteins having immunogenic properties for patients suffering TB and having had promising results in mice and non-human primates. Our approach has been based on a functional approach involving the pathogen-host interaction in the search for antigens to be included in designing an efficient, minimal, subunit-based anti-TB vaccine. This means that Mycobacterium tuberculosis has mainly been involved in studies and that lipoproteins represent an important kind of protein on the cell envelope which can also contribute towards this pathogen's virulence. This study has assessed the expression of four lipoproteins from M. tuberculosis H37Rv, that is, Rv1411c (LprG), Rv1911c (LppC), Rv2270 (LppN) and Rv3763 (LpqH), and the possible biological activity of peptides derived from these. Five peptides were found for these proteins which had high specific binding to both alveolar A549 epithelial cells and U937 monocyte-derived macrophages which were able to significantly inhibit mycobacterial entry to these cells in vitro. © 2014 John Wiley and Sons A/S.